2018
DOI: 10.1002/app.47110
|View full text |Cite
|
Sign up to set email alerts
|

Probing toughness of polycarbonate (PC: ductile and brittle)/polypropylene (PP) blends and talc‐triggered PC/PP brittle composites with diverse impact fracture parameters

Abstract: Polycarbonates (PCs) are commonly used as a blend and a composite to achieve pecuniary advantages and dimensional stability. While the toughness of a homogeneous PC matrix has been extensively investigated, examination for the toughness of heterogeneous blend systems such as PC/polypropylene (PP) blends has been limited. Furthermore, recent interest in highly flowable PCs (lowmolecular-weight PCs with low ductility) has surfaced due to the large and geometrically complex plastic parts. Herein, the toughness fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…However, above 10 phr PC or 10 phr PS, the shear strength was reduced, probably as a result of the uncompatibilizing behaviors between the phenoxy main matrix and amorphous polymer additives. Polymers are commonly incompatible and immiscible with one another [ 22 , 23 , 24 ]. As shown in Figure 4 , it was found that the compatibilizing agent (benzoic acid) reduced the interfacial energy among each component, thereby leading to compatibilizing effects.…”
Section: Resultsmentioning
confidence: 99%
“…However, above 10 phr PC or 10 phr PS, the shear strength was reduced, probably as a result of the uncompatibilizing behaviors between the phenoxy main matrix and amorphous polymer additives. Polymers are commonly incompatible and immiscible with one another [ 22 , 23 , 24 ]. As shown in Figure 4 , it was found that the compatibilizing agent (benzoic acid) reduced the interfacial energy among each component, thereby leading to compatibilizing effects.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to mechanical properties, the thermal properties of polymeric materials are of great importance due to their transition temperatures and crystallization behaviors. Even immiscible polymer blends are partially miscible with increasing ratio 11 and the miscibility (solubility) increases as a function of temperature. 24,25 As the temperature approaches the T g of blends during DSC scans, the miscibility gradually increases, thereby leading to lower T g than anticipated.…”
Section: Resultsmentioning
confidence: 99%
“…Polycarbonates (PCs) have been extensively used in numerous applications such as electronic and medical devices, due to their transparency, ductility, mechanical robustness, electrical properties, and reasonable price . To further reduce the price, PCs have been routinely mixed with inexpensive inorganic fillers, such as talc and CaCO 3 , or blended with polyolefins (also to further reduce the density) such as polyethylene and polypropylene (PP) . In addition to the monetary benefits, blend systems preferably reduce the viscosity, thereby enhancing processability of ductile PCs ( M w > ca.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the tensile strength and the apparent viscosity of the alloy increased signicantly and the sensitivity of the shear stress decreased with an increasing compatibilizer content. Li et al, Jang et al, and Alireza et al improved the mechanical properties of the PC/PP alloy by adding different proportions of a self-made compatibilizer, meanwhile, the cost of the alloy was reduced by adding nano calcium carbonate 4,5 or styreneethylene-butylene-styrene block copolymer. 6 In addition to formula studies on the PC/PP alloy, recently, extensive studies concerning different blending processing methods were also applied to the PC/PP alloy.…”
Section: Introductionmentioning
confidence: 99%